Kolaborasi Iman, Islam, Dan Ihsan: Menggapai Makna Hidup Yang Sesungguhnya - Muhammad Agam Nalf Saujani; Muhammad Andika Apriansyah; Aisyah Munadiya Khoiroh; Naila Nur Hikmah; Nur Wulan Ramadhani; Tiara Sisdayanti; Rika Widawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Faith, Islam, and ihsan are a unity that cannot be separated. With faith, Islam, and ihsan every Muslim can reach the true meaning of life. Faith, Islam, and ihsan become a combination of elements that are very important to live life. Therefore, Muslims who do not understand the combination of these three elements will not find the true meaning of life. Faith will give birth to Islam, and Islam will give birth to ihsan, from ihsan Muslims will be able to reach the true meaning of life. Faith has six pillars, namely: Faith in Allah, angels, book, messenger, last day, qada and qadar. Islam has five pillars, namely: Shahadat, prayer, zakat, fasting, pilgrimage for those who are able. Ihsan has four pillars, namely: Ihsan to Allah, self, fellow human beings, all creatures. The meaning of life for every human being is different, but the essence of the meaning of life desired by every human being is happiness, both happy in the world and happy in the hereafter.